O proposto e o vivido na relação socioambiental nos postos revendedores de combustíveis - Toffolo, Geliane (2013)
This work aims to bring out the result of the accomplished research with intends to check what are the problems that rules the actions and the contradictions in the socio and environmental practices at the urban Distributors and Gas Stations (DGSs) of the city of Francisco Beltrao/PR. So through a qualitative investigation, to understand how is manage the Environmental Education Process (EE) at these establishments. We have approached the concept of nature and aspects of its degradation and transformation. We have pointed out aspects of the public policy that would be interwoven of EE. It has also approached indicatives about Labor Union representative in the country, with the analysis of Collective Labor Conventions (CLC) of 2010/2011 and 2012/2013, a relationship signed between the Labor Union and Entities in their work relationship. We contemplate the different kinds of automotive fuels, its components and the activities developed, through the specific licensing legislation, installment, modernization and inspection, accomplished by CONAMA, CEMA and SEMA, by the technical rules accomplished by ABNT, INMETRO, NPT (Fire Station) and the dangers at these establishments. We have done an analysis of the location in relation to what is specified in the laws about installment, location and operation of DGSs; as well the water analysis in the rivers Lonqueador and Marrecas for the identification of product derived of fuels. We evaluate the proximity of some establishments and public routes close to such rivers. We have used for local analysis the CONAMA and SEMA resolutions in relation to proximity of DGSs to others business establishments, domestic buildings and water resources. It has been point out the environmental impacts as a result of some activities developed in the ground, in the waters, in the air and sounds, in the neighbourhood and to the workers. This essay is a diagnostic based on the laws and with our look on the proposed and the practiced in the relation socioenvironmental in the urban DGSs of Francisco Beltrao. It has brought some thoughts on the attitudes considered important in the relation of non formal EE, in the environment of these establishments.